Ø§Ø³ØªØ±Ø§ØªÙØ¬ÙØ© ÙÙØ§Ø±Ø© Ø§ÙÙØ±Ø§Ø¡Ø© ÙÙ ÙØ¸Ø±ÙØ© Ø³ØªÙÙÙÙ - Siregar, Zulli Umri (IZDIHAR, 2018)
Reading is a language skill through the interpretation of written symbols into comprehensible readable meanings in that the skill appears in the readers interaction with the readable text, its understanding, criticism, taste, and use in solving the problems encountered by the reader and its use in the behavior it produces during reading or after completion. To achieve this result, a strategy is needed for each individual and differs from one another. In order to upgrade the ability of this skill in the least time and effort, Stephens theory (STIFIn) provided an effective method of learning according to the most prominent intelligence engine that will help the individual more effective and efficient. By learning how to learn about this theory, you will also know the strategy of good reading skill that achieves the goal of this reading, and the researcher will search for how Stephens strategies of reading skills, especially for the sense of the relaxed and diastolic feeling.